The Model of Moderate Islamic Education Based on Integration Curriculum at Islamic International School PSM Grogol Kediri - Moh. Irmawan Jauhari; Siti Choiriyah; Ahmad Khoirul Mustamir; Muhammad Yunus; Mohammad Choirul Ibad (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This study aims to explore the development of a moderate Islamic education model rooted in local wisdom by integrating the Cambridge and Merdeka Curricula in Islamic schools in Kediri. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation at SDI Islamic International School PSM Kediri. Informants in this study included the headmaster, vice-curriculum, teachers, foundation advisors, guardians, and several students. The selection of informants was based on purposive sampling, thus narrowing the list of potential interviewees from the outset. Data analysis involved condensation, verification, and drawing conclusions, which were carried out simultaneously during data collection. The findings demonstrate a harmonious synthesis between global education and local Islamic values. The integration process applies inquiry-based learning from the Cambridge framework while instilling Javanese-Islamic values ​​such as reciprocal cooperation, empathy, and adaptability, while maintaining academic excellence. This study formulates a contextual model of Moderate Islamic Education Based on Local Wisdom, which balances global competence and spiritual character. This model contributes to Indonesia's vision of moderate Islamic education and provides practical insights for Islamic institutions in integrating global and local curricula.